SHADING LEVELS INFLUENCE THE PRODUCTION OF Mentha x villosa Huds. (MINT) SEEDLINGS - Wanderline Quaresma, Elias Vinícius; Pereira de Assis Otto, Rodrigo; Correia Santos, Cleberton; Milene Silverio, Juliana; de Souza Loli, Guilherme Henrique; Vieira, Maria do Carmo (Revista Brasileira de Engenharia de Biossistemas, 2021)
The mint (Mentha x villosa Huds., Lamiaceae) is a medicinal and aromatic plant, generally used on the preparation of teas and juices. Through this study it was assumed that levels of light interception of the seedlings production environment can influence vegetative propagation of mint. The experiment was carried out, evaluating four luminous availability based on the shading levels of 0% (full sun), 30%, 50% and 70%. The cuttings were collected in the morning, packed in a container with water, and standardized with 7.0 cm long and four leaves. Subsequently, 1/3 cutting was buried in substrate consisting of Dystrophic Red Latosol + Tropstrato® (3:1, v/v). The evaluations of non-destructive and destructive characteristics were performed at 75 days after the burial of the cuttings. In general, the mint seedlings showed values of survival > 80%. The highest height, root length and height/diameter ratio occurred in seedlings produced under 70% shade. On the other hand, seedlings produced in full sun (0%) have higher number of branches, leaf area, and fresh mass production of leaves, stem and roots. It is recommended for production of mint seedlings that their vegetative propagation by cuttings be made in environment under full sun